Financial accounting - Albrecht, Steve W. (McGraw-Hill, 1980)
The sixth edition interweaves analytical principles with real examples and real data from well-known companies. This text takes a business-activities approach to link accounting to what a business really does - operating, investing and financing. The result provides students with the practical skills they need to understand complex business issues and make smart strategic decisions